Biocompatible polymeric electrospun matrices: Micro–nanotopography effect on cell behavior. Issue 40 (6th April 2020) - Pisani, Silvia; Genta, Ida; Dorati, Rossella; Kavatzikidou, Paraskevi; Angelaki, Despoina; Manousaki, Aleka; Karali, Kanelina; Ranella, Anthi; Stratakis, Emmanuel; Conti, Bice
Abstract: This work reports a preliminary biological study performed on nanofibrous biocompatible polylactidecopolycaprolactone (PLA‐PCL) scaffolds intended for tissue regeneration. The aim was to evaluate how matrix surface topography affects cell adhesion and proliferation. Scaffolds prepared by electrospinning either equipped with plane or rotating mandrel collectors, were characterized for their surface topography and nanofiber size. Cell culture studies were carried out using mouse embryonic fibroblast cells lines (NIH‐3T3), as model for skin, murine neuroblastoma neuro‐2α cell line, as model for neuronal tissue, and mouse mesenchymal stem cells (MSCs), because of their differentiation ability. Imaging analysis by scanning electron microscope and laser scanning confocal microscopy together with cell viability (MTT, L 3‐(4, 5‐dymethiltiazol‐2‐y)‐2, 5 diphenyltetrazolium bromide) test, were performed on cell cultures at fixed time laps. The results showed that electrospun nanofibers supported growth and proliferation of the tested cell lines, but electrospun matrices obtained with rotating mandrel showed significantly higher cell viability that follows the orientation of electrospun nanofibers. Abstract :